Kolektif sebagai Institusi Kebudayaan Alternatif di Perkotaan Jawa: Telaah Infrastruktur Sosial - Khidir Marsanto Prawirosusanto (Antropologi Indonesia, 2019)
Collectives as a non-formal cultural institution began to emerge and widespread at around the 1998 Reformation. As a new form of cultural movement in Yogyakarta, collectives were different to formal cultural institutions, such as museums and art galleries, which mostly depend on financial support from the government, corporation, or some individual patrons. This article discusses the contemporary cultural organization domain with the case of collectives based in Yogyakarta. Some groups with characteristics of collectives were initiated in the urban sphere and run by young people. We comprehend this activism of collectives as a ‘cultural acts’ (laku budaya)—they ran various cultural activities continuously in fine arts, visual arts, music, food issues, and the practices of ‘knowledge production.’ Cultural acts collectivism could be identified through their creative and liberatory works oriented toward the creation of art works and/or critical publications. Their works were experimental and frequently expressed through various mediums. Likewise, the spaces they used were generally not tied to a strict administrative framework as in various formal cultural institutions. This ethnography intends to present the history and dynamics of the collectives of cultural acts in Yogyakarta, both as a group and individuals, which stood on the spirit to represent alternative ideas, resistance, and liberation as the basis to their values. In addition, it also discusses how the collectives of cultural acts took tactical means through social, cultural, and political functions to promote their values to the public.